Techniques For Extraction of Essential Oils From Plants: A Review - Rassem, Hesham H. A.; Nour, A. H.; R. M., Yunus (AENSI Publishing, 2016)
Background: Pure essential oils are derived from various part of the plants. These essential oils have a very high commercial value due to its properties. They are widely used in the various fields of industries, such as perfumery industries and pharmaceuticals. The essential oils for are primarily used in the perfumery industry and have a very high commercial value due to its therapeutic properties. Objective: study the techniques available to extract the essential oils from different plant and study the efficiency and the selectivity for this techniques. Results: The essential oils of the plant are composed of heat-sensitive chemical compounds, the use of steam distillation and Microwave-assisted extraction (MAE) techniques would inevitably inflict thermal degradation to the natural fragrance. In this experimental work, solvent extraction method was employed due to its mild extracting condition and lower operating cost. Ethanol was used as the solvent due to its high availability in the market. The extract compositions were compared using gas chromatography analysis. Conclusion: Extraction of essential oils out by different techniques and Innovative methods avoid shortcomings of content optional techniques friendly to environmental to avoid chemical risk, extraction time, consumption the solvents and obtain yield quality of essential oils.